Exosomes as drug delivery vehicle and contributor of resistance to anticancer drugs. (28th August 2020) - Chinnappan, Mahendran; Srivastava, Akhil; Amreddy, Narsireddy; Razaq, Mohammad; Pareek, Vipul; Ahmed, Rebaz; Mehta, Meghna; Peterson, Jo Elle; Munshi, Anupama; Ramesh, Rajagopal
Abstract: Exosomes are small membranous vesicles implicated in intercellular signalling. Through their uncanny ability to carry and deliver donor cellular cargo (biomolecules) to target cells, they exert a profound effect on the regular functioning of healthy cells and play a significant role in pathogenesis and progression of several diseases, including cancer. The composition and number of endogenously circulating exosomes frequently vary, which is often reflective of the pathophysiological status of the cell. Applicability of exosomes derived from normal cells as a drug carrier with or without modifying their intraluminal and surface components are generally tested. Conversely, exosomes also are reported to contribute to resistance towards several anti-cancer therapies. Therefore, it is necessary to carefully evaluate the role of exosomes in cancer progression, resistance and the potential use of exosomes as a delivery vehicle of cancer therapeutics. In this review, we summarize the recent advancements in the exploitation of exosomes as a drug delivery vehicle. We also discuss the role of exosomes in conferring resistance to anti-cancer therapeutics. While this review is focused on cancer, the exosome-based drug delivery and resistance is also applicable to other human diseases. Highlights: Exosomes are potential, natural drug delivery vehicles. Engineering of exosome cargo and surface receptors can make exosomes suitable for targeted drug delivery. Exosomes mediate resistance to multiple anti-cancer therapies.